2014
DOI: 10.1111/nep.12201
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes of trimethoprim–sulphamethoxazole as chemoprophylaxis for pneumocystis pneumonia in renal transplant recipients

Abstract: Use of chemoprophylaxis is an effective strategy in dealing with a PCP outbreak but can lead to a high number of complications. Rises in serum Cr can cause significant concern and increase in the number of investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
(60 reference statements)
0
36
0
Order By: Relevance
“…As often seen in clinical practice, Type-A ADRs contributed to a significant number of antibiotic allergy labels (10). Mitsides et al (11) reported similar rates of TMP-SMX ADR and discontinuation (38%) in 290 RTRs receiving PJP prophylaxis, predominantly due to SeCr rise. This rise is likely due to inhibition of tubular Cr secretion by trimethoprim which can result in reversible increases in SeCr higher than 35% in patients with pre-existing renal impairment (11) and, therefore, likely to recur on TMP-SMX rechallenge.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As often seen in clinical practice, Type-A ADRs contributed to a significant number of antibiotic allergy labels (10). Mitsides et al (11) reported similar rates of TMP-SMX ADR and discontinuation (38%) in 290 RTRs receiving PJP prophylaxis, predominantly due to SeCr rise. This rise is likely due to inhibition of tubular Cr secretion by trimethoprim which can result in reversible increases in SeCr higher than 35% in patients with pre-existing renal impairment (11) and, therefore, likely to recur on TMP-SMX rechallenge.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of patients were male (66%), having undergone their first transplant (91%), with a median ageadjusted Charlson comorbidity score of 4 (interquartile range [IQR]: 3, 6) ( Table 1). IgA nephropathy 23 (19) Polycystic kidney disease 13 (11) Reflux nephropathy 11 (9) Focal segmental glomerulosclerosis 10 (9) Glomerulonephritis (unspecified) 8 (7) Unknown cause 4 (3)…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we suggest a 6–12 month course of prophylaxis following either an episode of acute graft rejection or CMV infection. Although some complications have been reported with the use of TMP/SMX for PJP prophylaxis, major complications are relatively rare 28 ; therefore, the benefits of PJP prophylaxis outweigh the risks.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of TMP‐SMX for reasons of myelosuppression also appears unfounded, as rates of leukopenia in solid organ transplant cohorts when TMP‐SMX is employed as prophylaxis have been reported at less than 2% . Modern studies have suggested that TMP‐SMX therapy when employed as prophylaxis in hematological malignancy does not impact on the degree or duration of neutropenia .…”
Section: Discussionmentioning
confidence: 99%
“…13 We observed suboptimal G6PD screening in our dapsone patient cohort, with less than half under- The avoidance of TMP-SMX for reasons of myelosuppression also appears unfounded, as rates of leukopenia in solid organ transplant cohorts when TMP-SMX is employed as prophylaxis have been reported at less than 2%. 16,17 Modern studies have suggested that TMP-SMX therapy when employed as prophylaxis in hematological malignancy does not impact on the degree or duration of neutropenia. 18 A recent Cochrane review of PJP prophylaxis in the non-HIV setting found no difference in adverse events requiring discontinuation when comparing TMP-SMX to no treatment or placebo.…”
Section: Discussionmentioning
confidence: 99%